ISLAMIC PURITANISM MOVEMENT OF MUHAMMAD IBN ‘ABD AL-WAHHAB: Portrait of The Institutionalization of Islamic Ideology in State Space - Ihwan Agustono (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2023)
Around the 18th century, Muslims experienced a period of intellectual stagnation as a result of ijtihad, which appeared to have been tightly shut. Furthermore, heretical and khurafat traditions are becoming increasingly common. Consequently, Muslims drifted further away from the Quran's teachings and the Prophet's Sunnah. These kinds of circumstances motivated Muhammad ibn ‘Abd al-Wahhab to respond by attempting to restore the original spirit of Islamic revivalism (Tajdid) by going back to the pure teachings of Tawhid, as his predecessors, Ahmad bin Hanbal and Ibn Taymiyyah, had done previously. This paper aims to examine the characteristics of Muhammad ibn ‘Abd al-Wahhab’s purification of the Tauhid and his role in the establishment of the Kingdom of Saudi Arabia, which was regarded as one of the most successful ideologies institutionalizing the puritanical Islamic revival has ever seen in the history of contemporary Islamic politics. This work applies qualitative methodology with a historical approach, carried out by collecting data from Ibn ‘Abd al-Wahhab’s book as a primary source and other related books, journals, and articles as secondary sources. The research found that Ibn ‘Abd al-Wahhab's tajdid began as a religious movement and rose to prominence after collaborating with Muhammad ibn Saud's political effort. After the foundation of the Kingdom of Saudi Arabia a century and a half later, this idea was successfully established as a state-owned ideology. The birth of the kingdom was inextricably connected to the growth of Nationalism in the Islamic world as a result of European colonialism.